Islam neo-imperialisme dan terorisme : perspektif hukum internasional dan nasional - Thontowi, Jawahir; Iskandar, Pranoto (Yogyakarta : UII Press, 2004)
Human rights abuse in stereotyping Islam with terrorism in Indonesia; legal perspectives
Daftar pustaka: p. 191-196.
Keywords: Islam and terrorism; Terrorism -- Religious aspects -- Islam; Criminal law (Islamic law)